Birth of a Regulatory Long Non-coding RNA/Gene, linc-UR-UB - Delihas, Nicholas (Frontiers in Genetics, 2021)
The origin of genes has been a major topic of research for many years, albeit in some cases it has been a difficult process to elucidate. Insightful is a recent publication that experimentally shows how one lincRNA gene, linc-UR-UB was born. This gene is regulated in a complex manner in male germ cells during spermatogenesis and is believed to participate in the regulation of levels of the ubiquitin specific peptidase USP18 mRNA. . The process of formation of linc-UR-UB appears relatively simple. It involves a transcription read through from an upstream gene to a downstream functional element, the USP18 3' UTR sequence. This small element also shares the same sequence as the 3’ ends of the lincRNA FAM247 family genes. In addition to linc-UR-UB, it is possible that other genes formed in a similar fashion that involves a genomic sequence read through to a functional element.